A New Approach to Solving Linear Fractional Programming Problem with Rough Interval Coefficients in the Objective Function - Mustafa, Rebaz B.; Sulaiman, Nejmaddin A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
This paper presents a linear fractional programming problem (LFPP) with rough interval coefficients (RICs) in the objective function. It shows that the LFPP with RICs in the objective function can be converted into a linear programming problem (LPP) with RICs by using the variable transformations. To solve this problem, we will make two LPP with interval coefficients (ICs). Next, those four LPPs can be constructed under these assumptions; the LPPs can be solved by the classical simplex method and used with MS Excel Solver. There is also argumentation about solving this type of linear fractional optimization programming problem. The derived theory can be applied to several numerical examples with its details, but we show only two examples for promising.